2014
DOI: 10.2753/csa2162-0555460403
|View full text |Cite
|
Sign up to set email alerts
|

Independent Freshman Admission and Educational Inequality in the Access to Elite Higher Education

Abstract: the anonymous reviewers for comments and suggestions; and Yang Chen for her assistance in data analysis.Abstract: Over the past decade, China has undertaken a significant institutional reform of its admission system in elite higher education (namely, Independent Freshman Admission, IFA), adopting a multistage selection strategy characterized by recommendation and interviews as an alternative channel of admission to the national college entrance examination (gaokao). Using IFA administrative data from Peking Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…However, this policy is "unfair" in that, first, it has posed major obstacles to migrant students in large cities, and the rural-urban status contributes to unequal results in educational attainment (Treiman 2013, Liu et al 2014. As previous research has shown, this policy reduces the motivation of migrant students, making them less competitive even if they return to their hometown to study (Xiong 2015).…”
Section: Hukou System Education Of Migrant Children and Educationalmentioning
confidence: 99%
“…However, this policy is "unfair" in that, first, it has posed major obstacles to migrant students in large cities, and the rural-urban status contributes to unequal results in educational attainment (Treiman 2013, Liu et al 2014. As previous research has shown, this policy reduces the motivation of migrant students, making them less competitive even if they return to their hometown to study (Xiong 2015).…”
Section: Hukou System Education Of Migrant Children and Educationalmentioning
confidence: 99%
“…For example, with a longitudinal data of 2744 adolescents, Morris et al (2018) found that children from low SES families tended to live in low SES neighborhoods, causing a higher tendency for them to take up smoking. With the Independent Freshman Admission administrative data from an elite university (i.e., Peking University in China), Liu et al (2014) found that adolescents in high SES families had more chances to pass the selection process to enter these universities. In such circumstances, with less social capital, parental involvement is more important for adolescents in low SES families.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2004, IFA has been widely adopted by most elite colleges as another recruitment channel in China. As proposed by Liu et al (2014), privileged groups could maintain their advantages through Independent Freshman Admission. The admission procedure and criteria of IFA are mainly designed by universities and are less transparent compared with the College Entrance Examination.…”
Section: College Admission Procedures In Chinamentioning
confidence: 99%
“…Another form of preferential treatment is Independent Freshman Admission (IFA). As the alternative channel of admission, IFA is a university-specific selection strategy based on non-standard criteria such as application materials, references, and interviews, and designed to recruit students with comprehensive qualities and special talents (Liu et al., 2014). Since 2004, IFA has been widely adopted by most elite colleges as another recruitment channel in China.…”
Section: Institutional Backgroundmentioning
confidence: 99%
See 1 more Smart Citation